Review of seismological investigations related to 1998 Mw5.6 and 2004 Mw5.2 earthquakes in Krn Mountains - Gosar, Andrej (Geologija, 2019)
Overview of extensive seismological studies of Krn Mountains earthquakes performed in two decades is given. Detailed macroseismic studies by using a new European Macroseismic Scale EMS-98 showed large variations in damage to buildings due to the influence of very heterogeneous sediments and partly also due to the differences in source radiation pattern. Site effects were carefully studied and it was proven by microtremor HVSR method that soil-structure resonance effects severely enhanced the damage in many places. Particularly important were seismotectonic studies based mainly on focal mechanisms and distribution of aftershocks. Combined with geological data these studies pointed to the complex structure of segmented Ravne fault, which is growing by interactions between individual fault segments. A wider area is characterised by a kinematic transition between Dinaric (NW-SE) strike-slip faults in W Slovenia and E-W trending Alpine structures with predominantly reverse faulting in Friuli. Other investigations included static stress changes on neighbouring faults, analyses of the time decay of extensive aftershock sequences and magnitude-frequency relations. All these studies have significantly fostered seismological research in Slovenia and have enhanced international cooperation. Following the 1998 earthquake a modern national seismological network was built composed of 26 stations equipped with broadband sensors, accelerometers and high-resolution digitizers. Together with cross-border exchange of real-time data the seismological monitoring has been significantly improved.